Sales essentials : the tools you need at every stage to close more deals and crush your quota - Salman, Rana (McGraw Hill-Ascent Audio, 2023)
With so much focus put into making a sale, many professionals find they need help improving the crucial points that come before and after the sale. In Sales Essentials, you'll find the comprehensive, up-to-date information you need to improve your skills at every point of the sales process. - PART I: THE ESSENTIALS explores the foundation for the sales experience-the human connection. It also dives into common challenges sellers encounter and actionable insights to address them, followed by the characteristics and attributes associated with the most successful salespeople. - PART II: THE ESSENTIALS APPLIED gives you tools to use before, during, and after the sale, including tips on prospecting, preparing, and conducting the discovery meetings, qualifying in and out, getting the most out of follow-up meetings, closing deals, and setting up accounts for success and expansion. Real, raw, and direct, you'll learn from someone who has been in the sales trenches for years-no fluff! - PART III: BEYOND THE ESSENTIALS offers even more hands-on advice about the human side of sales-from dealing with rejection and self-doubt to learning about specific tactics to help protect your mental health.